Clinical case review: A method to improve identification of true clinical and radiographic pneumonia in children meeting the World Health Organization definition for pneumonia - Puumalainen, Taneli; Quiambao, Beatriz; Abucejo-Ladesma, Erma; Lupisan, Socorro; Heiskanen-Kosma, Tarja; Ruutu, Petri; Lucero, Marilla G; Nohynek, Hanna; Simoes, Eric AF; Riley, Ian (BMC infectious diseases, 2008)
Background The World Health Organization's (WHO) case definition for childhood pneumonia, composed of simple clinical signs of cough, difficult breathing and fast breathing, is widely used in resource poor settings to guide management of acute respiratory infections. The definition is also commonly used as an entry criteria or endpoint in different intervention and disease burden studies. Methods A group of paediatricians conducted a retrospective review of clinical and laboratory data including C-reactive protein concentration and chest radiograph findings among Filipino children hospitalised in the Bohol Regional Hospital who were enrolled in a pneumococcal vaccine efficacy study and had an episode of respiratory disease fulfilling the WHO case definition for clinical pneumonia. Our aim was to evaluate which disease entities the WHO definition actually captures and what is the probable aetiology of respiratory infections among these episodes diagnosed in this population. Results Among the 12,194 children enrolled to the vaccine study we recorded 1,195 disease episodes leading to hospitalisation which fulfilled the WHO criteria for pneumonia. In total, 34% of these episodes showed radiographic evidence of pneumonia and 11% were classified as definitive or probable bacterial pneumonia. Over 95% of episodes of WHO-defined severe pneumonia (with chest indrawing) had an acute lower respiratory infection as final diagnosis whereas 34% of those with non-severe clinical pneumonia had gastroenteritis or other non-respiratory infection as main cause of hospitalisation. Conclusion The WHO definition for severe pneumonia shows high specificity for acute lower respiratory infection and provides a tool to compare the total burden of lower respiratory infections in different settings. Trial registration ISRCTN62323832